US emergency nurses' perceptions of challenges and facilitators in the management of behavioural health patients in the emergency department: A mixed-methods study. Issue 3 (August 2015) - Wolf, Lisa A.; Perhats, Cydne; Delao, Altair M.
Summary Background Behavioural health patients often have longer lengths of stay in the emergency department compared with general medical patients, and their modalities of care are not well documented. This study's purpose is to describe US emergency nurses' estimates of lengths of stay for behavioural health patients, explore factors affecting length of stay, and assess nurses' perceptions of their skills, beliefs/attitudes, and confidence in caring for this population. Methods Using a mixed-methods design with demographically-diverse samples of emergency nurses, survey data (N = 1229) were analysed using descriptive statistics, correlation coefficients, and linear regression. Focus group participant data (N = 20) were analysed for themes using constant comparison. Results Findings suggest that shorter lengths of stay are associated with higher levels of perceived nursing confidence/preparation to care for this population, along with the availability of appropriate resources and protocols/standards of care (p = 0.01). Longer lengths of stay are associated with an absence of dedicated inpatient space for managing the care of these patients. Conclusions Participants note a lack of education, resources, and treatment options tailored to the delivery of safe, effective care for behavioural health patients. The use of trained specialists and additional guidelines/protocols may help move patients through the emergency department faster and with greater surety.